Du burlesque chez Correas ou quand la grossièreté de la sagesse populaire devient un procédé humoristique - Sonia Fournet-Pérot (Les Cahiers de Framespa)
Proverbs were an omnipresent component of Medieval culture and were very much appreciated by courtiers and educated people until the 16th century. They became part and parcel of popular wisdom in the 17th and 18th centuries. Proof of it is Gonzalo Correas's refranero, dated 1627 and which comprehends 25,000 occurrences. Popular as it may have been, proverbial language remained a teaching made explicit along formal standards and as such was by nature only liable to convey serious matter. However, many sequences came to integrate humour very often through the medium of coarse language, incongruously enough. That two separate signifiers, refrán vs proverbio, existed testified to a potential distinction between couth and uncouth utterances. In this paper, we will describe these burlesque proverbs and classify them from thematic, semantic and rhetorical viewpoints. This classification will help us examine the underlying pragmatic mechanisms that allow coarse utterances to take on a humourous tinge in the very specific context of proverbial matter.